Hotel Analytics: The Case for Reverse Competitive Sets. (November 2022) - Schwartz, Zvi; Webb, Timothy; Ma, Jing
Hotel industry practitioners and scholars expressed concerns regarding the reliability of the commonly used comparative performance indices, given the subjective nature of the competitive (comp) sets. This study explores the potential of two alternative comp sets: reverse and name-back. It is demonstrated that they have a higher level of integrity as they moderate the values of a traditional comp set–based RevPAR (revenue per available room) index, are simple to implement, and are more dynamic. The study shows analytically and empirically that the two are likely to mitigate biases and that the reverse comp set appears to be more effective than the name-back. Multiple practical implications are outlined and discussed.